Gagal Spinal pada Pasien Operasi Amputasi Transfemoral dengan Debridemen dan Penatalaksanaannya - Sudadi; Maryani, Nova; Artika, I Gusti Ngurah Rai (Jurnal Komplikasi Anestesi, 2017)
A man 64 years old had a traffic accident 12 hours ago, resulting in crush injury on regio left femur and cruris. This man has fasted and for 8 hours and was planned to undergo debridement and transfemoral amputation surgery by orthopedics. The hemodynamic profile of this patient preoperative: stable with HB 8.4, had two colfs of PRC blood transfusion. Vital sign BP 110/55, HR 110x/minute, RR 22x/minute, SpO2 97%. The anesthesia technique planned for the surgery is spinal block anasthesia. Fluid preloading RL 500 ml, intravenous analgesics fentanyl 25 mcq, sitting position, spinal anesthesia L4-L5, CSF (+), blood (-), agent: bupivacaine 0,5 % hyperbaric 15 mg + fentanyl 25 mcq, aspiration (+) barbotage until 4cc. Thus, supine position after spinal anesthesia. Pin Prick result, Sensoric test (-), Motoric Bromage 0, evaluated until 10 minutes, just parasthesia. Pin prick, result sensoric test no sensoric. Block declared failed, conversion to General Anesthesia LMA. Operation held for 2 hours, post-operative patient transfers to High Unit Care.